Utilizing a transport management system to reduce the carbon footprint of transportation in a global marine and energy technology organization - Nojosaho, Milja (My University, 2023)
The importance of sustainable development is constantly growing, and sustainability has be- come a desired characteristic among companies. Today, this is highlighted by various sustaina- bility goals that companies commit to meet the requirements of climate laws and consumers' more ecological choices along with the volume of research conducted on the matter. Companies must consider the carbon footprint of their operations to achieve their aim of lowering emis- sions. Because the transportation industry is one of the largest producers of carbon dioxide emissions worldwide, focusing on it enables huge emission reductions across supply chains. This master's thesis is conducted as a case study for a company. The objective of the thesis is to find out the most effective ways to utilize a transport management system used by the case company to reduce the carbon footprint caused by the transportation of the incoming material flow. The thesis aims to investigate what factors contribute to the carbon footprint of transpor- tation in the case company, how emissions can be measured using a transport management system, and how its utilization affects time, cost, and reliability when choosing more environ- mentally friendly modes of transportation. To achieve these objectives, internal interviews were performed at the case company, and the features of the transport management system were familiarized. The research is a qualitative case study. The theoretical part of the research focuses on the var- ious modes of freight transportation and the related emissions, as well as the functions and role of transport management systems in measuring and controlling emissions from transportation. The objective of the empirical part of the research is to describe the current transportation pro- cesses of the case company and the generation of the carbon footprint of transportation and to examine how the transport management system is currently utilized in the case company. The research methods include a literature review, interviews, and presentations related to the transport management system. The research provided insight into the elements of the carbon footprint of transportation in the case company and the potential for more effective utilization of the transport management sys- tem in measuring and reducing emissions. The main sources of emissions in the case company were discovered to be air freight and road freight transportation. The transport management system has been used to support the transportation process in the background, and the system offers several features that have not yet been fully used, that allow emissions to be measured and decreased when effectively utilized. Data collection and integration with the transport man- agement system make it possible to obtain comparable reports that can be used to guide future strategic choices regarding transportation and transportation providers.

Kestävän kehityksen merkitys on jatkuvassa kasvussa ja kestävyydestä on tullut tavoiteltava omi- naisuus yritysten keskuudessa. Tämä korostuu nykypäivänä erilaisilla kestävillä tavoitteilla, joi- hin yritykset sitoutuvat vastatakseen ilmastolakien vaatimuksiin ja kuluttajien ekologisempiin valintoihin, ja aiheesta on tehty myös useita tutkimuksia. Saavuttaakseen päämääränsä päästö- jen vähentämiseksi, yritysten on kiinnitettävä huomiota toimintansa hiilijalanjälkeen. Kuljetus- sektori on yksi suurimmista hiilidioksidipäästöjen aiheuttajista maailmassa ja siksi siihen keskit- tymällä on mahdollista saavuttaa merkittäviäkin päästövähennyksiä toimitusketjuissa. Tämä pro gradu -tutkielma on toteutettu tapaustutkimuksena yritykselle. Tutkielman tavoit- teena on selvittää tehokkaimmat tavat hyödyntää tapausyrityksen käyttämää kuljetustenhallin- tajärjestelmää niin, että on mahdollista pienentää saapuvan materiaalin kuljetuksista syntyvää hiilijalanjälkeä. Lisäksi tavoitteena on tutkia, mistä kuljetusten hiilijalanjälki tapausyrityksessä muodostuu, miten päästöjä on mahdollista mitata kuljetustenhallintajärjestelmän avulla ja mil- laisia vaikutuksia sen hyödyntämisellä on aikaan, kustannuksiin ja luotettavuuteen, kun valitaan ympäristöystävällisempiä kuljetusmuotoja. Näiden tavoitteiden saavuttamiseksi on suoritettu tapausyrityksen sisäisiä haastatteluja sekä perehdytty käytössä olevan kuljetustenhallintajärjes- telmän tarjoamiin ominaisuuksiin. Tutkimus on kvalitatiivinen tapaustutkimus. Tutkimuksen teoreettinen osuus käsittelee rahtikul- jetusten eri muotoja ja niihin liittyviä päästöjä sekä kuljetustenhallintajärjestelmien toimintaa ja roolia kuljetuksista syntyvien päästöjen mittaamisessa ja hallitsemisessa. Tutkielman empiiri- sessä osuudessa on tarkoitus kuvata tapausyrityksen nykyisiä kuljetusprosesseja ja kuljetusten hiilijalanjäljen muodostumista sekä tarkastella, miten kuljetustenhallintajärjestelmää tutkimus- hetkellä hyödynnetään tapausyrityksessä. Tutkielman tiedonkeruumenetelmiä ovat kirjallisuus- katsaus, haastattelut ja kuljetustenhallintajärjestelmään liittyvät esitelmät ja esitysmateriaalit. Tuloksena saatiin näkemys siitä, mistä kuljetusten hiilijalanjälki tapausyrityksessä muodostuu ja tunnistettiin mahdollisuuksia kuljetustenhallintajärjestelmän tehokkaammalle hyödyntämiselle päästöjen mittaamisessa ja vähentämisessä. Tapausyrityksen suurimmiksi päästöjen aiheutta- jiksi kuljetusmuodoista todettiin lentorahti ja maantiekuljetukset. Kuljetustenhallintajärjestel- mää on hyödynnetty tapausyrityksessä kuljetusprosessin taustalla ja järjestelmässä on useita ominaisuuksia, joita ei vielä ole hyödynnetty ja jotka mahdollistavat päästöjen mittaamisen ja vähentämisen, kun niitä hyödynnetään tehokkaasti. Dataa keräämällä ja yhdistämällä sen kulje- tustenhallintajärjestelmään on mahdollista saada vertailukelpoisia raportteja, joiden perusteella tapausyritys voi jatkossa tehdä strategisia päätöksiä kuljetuksiin ja kuljetusyrityksiin liittyen.
Keywords: päästöt; kuljetus; ympäristövaikutukset; hiilijalanjälki; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management